Estimación del consumo energético de buses urbanos en rutas preestablecidas en la ciudad de Loja - Panchana Torres, Bryan Alexander (2023)
Calculations are presented for the estimation of energy consumption in urban buses with the highest influx of passengers in the city of Loja, corresponding to lines L2 (Argelia - Sauces Norte), L8 (Ciudad Victoria - Carigan), L11 (Bolonia - Tierras Coloradas). The investigation begins with the compilation of the database by monitoring the units or buses of the Hino brand, model AK, from the beginning of the journey to the end of it, with the application for cell phones (Torque Pro), of which the data of, altitude, latitude, longitude and speed were obtained, at a frequency of 1 Hz. The monitoring is carried out during 25 round trips for each route. To obtain the dynamic drag coefficients and rolling resistance; the road load measurement test was carried out using the descent technique called Coast Down and a subsequent optimization process using the generalized gradient method no linear. Once the database was established the calculation of traction energy consumption or demand was made based on the longitudinal dynamics of the vehicle. The results obtained from the Coast Down test show an aerodynamic drag coefficient or of 0.772 ± 0.00583 and a rolling resistance coefficient of 0.0907 ± 0.0233. The analysis of energy consumption for each of the lines involved in the study is determined by the conditions of the route and other factors, obtaining that the energy consumption for line L2 was 25.71 kWh, for line L8 a consumption energy consumption of 50.36 kWh and line L11 an energy consumption of 48.77 kWh. Keywords: Energy consumption, try Coast Down, driving cycles, torque application pro.